PRODUKSI BIOGAS DARI UMBI SINGKONG DENGAN KOTORAN SAPI SEBAGAI STARTER - Ucok Hasiholan; Agus Haryanto; Sigit Prabawa (The University of Lampung, 2016)
Biogas technology is easy to be implemented and has a lot of raw materials available in various forms such aslivestock waste, agricultural waste, industrial waste and the like which has high organic matter. This study aimedto determine the biogas production, biogas yield, hydraulic retention time, and the quality of biogas made fromcassava and cassava leaves with cow dung as a starter. The experiments were performed using a completelyrandomized design (CRD) with four treatments and four repetitions. Substrate composition of cassava leaves,cassava tubers, and cow dung is A (15: 0: 85), B (0:15:85), C (0:25:75), and D (0:35:65). Variance analysisperformed using SAS statistical program. The results showed that the composition of the substrate significantlyaffect the total production of biogas, but did not significantly affect the productivity of biogas. The highestproduction of biogas obtained from C treatment amounting to 6,995 ml. The average yield of biogas is 130.85mL/g TVS. Biogas produced from treatment C and D burn easily and leave a blue flame indicates adequate contentof CH4 in biogas as a fuel.Keywords:biogas, cassava, cowdung,yield